Comparison of Functional Outcome and Union of Proximal Humerus Fractures Fixed with Philos Plate Versus T Plate - Zahid Iqbal, Muhammad Imran Haider, Muhammad Imran Anjum, Muhammad Ishfaq Mazari, Rana Muhammad Javaid Afzal, Rana Shahid Waseem Ronaq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The purpose of this study was to evaluate the differences between PHILOS and T plates in terms of functional recovery and fracture union after proximal humerus fractures. Study Design: Prospective study Place and Duration: Bahawal Victoria Hospital, Bawalpur/Nishtar Hospital, Nishtar Medical University, Multan. Jun 2020-January 2022 Methods: There were a total of 48 patients, both sexes, ranging in age from 20 to 75. All the included patients had humerus fractures and admitted to hospital for operation. Age, sex, BMI, fracture aetiology, and fracture side were recorded together with other pertinent demographic information after obtaining written consent from the patients. Patients were equally divided in two groups. Group I received Proximal Humerus Internal Locking System (PHILOS) in 24 cases and group II 24 cases received T platting. Patients were followed for 12-months. Post-operative functional and union outcomes among both groups were assessed. We used SPSS 26.0 to analyze all data. Results: There were 36 (75%) male patients and 12 (25%) females among all cases. In group I mean age was 47.9±8.42 years with mean BMI 23.6±4.23 kg/m2 while in group II mean age was 50.3±7.29 years and had mean BMI 24.5±3.42 kg/m2.RTA was the most common etiology found in group I 13 cases and 12 cases in group II. Right was the most common affected side among all cases 15 in group I and 14 in group II. Mean operative time of T plates 131.3±12.16 minutes were higher as compared to PHILOS 121.2±17.40 minutes. Blood loss was also higher in T plates as compared to PHILOS with p value <0.003. As per functional results, group I showed higher frequency of excellent and good results (16.7%, 54.2%) as compared to group II (8.3%, 41.7%). Mean union time was lower in group I 11.6±5.33 weeks as compared to group II 15.8±2.52 weeks. Post-operative complications by using T plates were found higher 6 (25%) as compared to group PHILOS group 3 (12.5%). Conclusion: We concluded in this study that PHILOS platting for the fixation of proximal humerus fractures were effective and useful in terms of less blood loss, less operative time, less union time and higher number of excellent and good results as compared to T platting. Except this complications were also found lower in PHILOS platting group. Keywords: Proximal Humerus Fracture, PHILOS Plate, T Plate, Complications, Functional outcomes